Metabolic profiling reveals the importance of arginine metabolism via the arginine deiminase pathway in vancomycin-intermediate S. aureus - Tan, JK; Tan, XE; Neoh, HM (Penerbit Universiti Kebangsaan Malaysia, 2024)
Gene mutations located in VraSR and GraSR, two-component regulatory systems have been reported to cause vancomycin resistance in vancomycin-intermediate Staphylococcus aureus (VISA). Subsequent comparative proteomic profiling between vancomycin-susceptible S. aureus (VSSA) and VISAs of the Mu50 genetic lineage revealed up-regulated level of catabolic ornithine carbamoyltransferase (ArcB) in the latter, suggesting a role of arginine catabolism in VISA development. This study aimed to further investigate metabolic pathways associated with VISA development using liquid chromatography mass spectrometry (LCMS)-based untargeted metabolomic profiling. Metabolite profiles were compared among 3 isogenic strains of the Mu50 lineage: Mu50Ω (VSSA), Mu50Ω-vraSm (VISA) and Mu50Ω-vraSm-graRm (VISA). Intracellular levels of α-hydroxyglutaric acid, choline, lysine, malic acid, N-acetylornithine, nicotinamide, and cystathionine were found to be significantly different between VISAs compared to VSSA. VISA cells were found to have lower levels of intracellular citrulline and extracellular arginine, with higher extracellular level of ornithine compared to VSSA. These differences in metabolite levels between VISA and VSSA suggested the importance of arginine metabolism. Activation of the arginine deiminase pathway (ADI) in VISAs of the Mu50 lineage could be further explored as a target for antibiotic development.